2004
DOI: 10.1051/limn/2004015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enzyme biomarkers in freshwater invertebrates from Taro and Ticino river, Italy

Abstract: Benthic macroinvertebrates are an essential component of freshwater environments. The ecotoxicological risk of benthic communities, estimated through the assay of biochemical markers, can be used as an early warning signal for environment alterations. In this work the activities of a number of enzymes, regarded as potential biomarker of exposure to pollutants (catalase, acetylcholinesterase, glutathione-S-transferase) was determined in homogenates of whole organisms. Specimens were collected in the rivers Taro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
5
29
1
Order By: Relevance
“…However, we found all the fundamental antioxidant enzymes are active in our studied aquatic insect species and that there are significant differences among these taxa. This fact has been previously noted also by Berra et al (2004). In particular, the GPX activity in insects was reported for nymphs of different species of Plecoptera (Sanz et al, 2010(Sanz et al, , 2014.…”
Section: Antioxidant Capacitysupporting
confidence: 77%
See 1 more Smart Citation
“…However, we found all the fundamental antioxidant enzymes are active in our studied aquatic insect species and that there are significant differences among these taxa. This fact has been previously noted also by Berra et al (2004). In particular, the GPX activity in insects was reported for nymphs of different species of Plecoptera (Sanz et al, 2010(Sanz et al, , 2014.…”
Section: Antioxidant Capacitysupporting
confidence: 77%
“…is notable for its high G6PDH activity, an enzyme in the pentose phosphate pathway with a high reduction power responsible for several functions in the animal organism. Berra et al (2004) noted that G6PDH activity is very low or undetectable in most taxa, including Plecoptera. In our work, the lowest values corresponded to I. morenica, C. erythraea and Hydropsyche sp., species belonging to three taxonomic groups, Plecoptera, Odonata and Trichoptera, respectively.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…Berra et al [14] collected various aquatic insects, a crustacean, and an annelid species from Taro and Ticino Rivers in northern Italy, and found significant differences among taxa in the specific activity of AChE and GST. With respect to season, they reported that for most taxa, AChE activity changed seasonally three to five times, while GST had less variability.…”
Section: Inter-and Intra-specific Variationsmentioning
confidence: 99%
“…Berra et al [41] have evaluated the basal-level activities of three enzymes (catalase, acetylcholinesterase and GST) in order to investigate potential biomarkers of exposure to pollutants in different species of macroinvertebrates [Insecta (Diptera, Plecoptera, Odonata, Ephemeroptera and Trichoptera); Crustacea (Gammaridae); and, Oligochaeta (Lumbricidae)] in two Italian rivers. Results showed that the responsiveness of the enzymes differed among taxa of the same community, and from taxon to taxon from different river systems.…”
Section: Early Warning In the Field: Biomarkersmentioning
confidence: 99%